Vibrational frequency analysis of CH3Cl molecule; ab initio study - Subedi, Shiba; Nakarmi, Jeevan Jyoti (Himalayan Physics, 2015)
First-principles calculations implemented by Gaussian 09 sets of programs has been performed in order to study the stability, electronic properties, nature of bonding and vibrational frequency assignments for CH3Cl molecule using QCISD levels of approximation with the choice of basis set 6-31G(d, p). Quantum Theory of Atoms In Molecule (QTAIM) approach has been adopted for bonding analysis and HOMO, LUMO energies were taken as the central aspects for discussing the chemical reactivity of the studied system. The vibrational frequency shift due to isotopic substitution of C-atom and Cl-atom in title molecule has been discussed. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 142-145